A Three Tier Strategy for Successful European Countries in the Nineties - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2003)
The economic performance of European countries was in general disappointing in the nineties. However, country difference increased, as it was that in some European countries economic growth and productivity accelerated or could match US rates. This paper uses a broad set of performance indicators - plus some deliberate choices - to carve out a group of successful countries and to compare their economic strategy to that of the low performing large European economies. The analysis shows that these successful countries used a policy mixture of cost cutting, improving institutions, and investing in future growth. We consider the first two strategy elements as preconditions, the investment in growth drivers as the sufficient condition for longrun growth. The difference between top and low performers is the largest for investments into determinants of future growth such as research, education and the diffusion of new technologies. The top countries surpassed the large European countries in research outlays in 1988 and are steadily increasing their lead since that time. The top performers are welfare states with a comprehensive social net, which they maintained in principle, while improving the incentive structure and the inner workings of their institutions. The results are not in line with the usual twin hypotheses that high welfare costs and insufficient labour market flexibility are responsible for European underperformance.
Keywords: E60; O11; O40; 330; Wirtschaftswachstum; Wirtschaftspolitik; Internationaler Wettbewerb; EU-Staaten